El proceso de terapia ocupacional en la unidad geriátrica de agudos del HCUCh - Gajardo J., Jean (Revista Hospital Clínico Universidad de Chile, 2008)
Hospitalization may have a different meaning and impact, if we compare a young population to an aged one. For aged people, being hospitalized usually has negative consequences for functionality and independence in activities of daily life (ADL). This problem relates to one of the purposes that the professional team of the Acute Geriatric Unit (AGU) at University of Chile’s Clinical Hospital (HCUCh) has for its patients. At the AGU, professionals including Geriatricians, Pharmacist, Neuropsychologist, and Neurologist, provide reatment for elders having the prevention and improvement of functionality as main goals of treatment and indicators for discharge. Currently, an Occupational Therapist from the Occupational Therapy (OT) Department at HCUCh is also included as part of the professional team of the AGU. The OT intervention at the AGU represents a requires a distinct approach: it must consider geriatric knowledge and gerontology. This article brings a theoretical revision about the needs of patients at the AGU, which at the same time represent problematics to be treated by OT. It includes also a description of the process of Occupational Therapy at the AGU with results obtained so far.